Exploring the great migration of the Serengeti - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 2007)
Report on trip to see the wildebeest migration in the Serengeti, Tanzania. In the vast wildebeest migration, a million and a half ungainly antelope migrate a thousand miles showing an endurance that belies their clumsy appearance. The American West once had a more vast migration: over 30 million bison, and we lost that greater wonder. Tanzanians, among the poorer nations, are quite resolved to keep the wildebeest free on their landscape. Older than human history, today this is the greatest wildlife show on Earth.
Keywords: migration; Tanzania; wildebeest; Serengeti